2020
DOI: 10.3390/antiox9100965
|View full text |Cite
|
Sign up to set email alerts
|

The Late-Stage Protective Effect of Mito-TEMPO against Acetaminophen-Induced Hepatotoxicity in Mouse and Three-Dimensional Cell Culture Models

Abstract: An overdose of acetaminophen (APAP), the most common cause of acute liver injury, induces oxidative stress that subsequently causes mitochondrial impairment and hepatic necroptosis. N-acetyl-L-cysteine (NAC), the only recognized drug against APAP hepatotoxicity, is less effective the later it is administered. This study evaluated the protective effect of mitochondria-specific Mito-TEMPO (Mito-T) on APAP-induced acute liver injury in C57BL/6J male mice, and a three dimensional (3D)-cell culture model containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 69 publications
1
13
0
Order By: Relevance
“…Mito-TEMPO (Sigma, USA) was intraperitoneally injected at a dose of 20 mg/kg body weight 1 h prior to LPS injection. The dosage of Mito-TEMPO is comparable with previous studies [ 28 , 29 ]. Animals were euthanized 24 h after LPS administration, and whole blood and liver samples were harvested for analysis.…”
Section: Methodssupporting
confidence: 88%
“…Mito-TEMPO (Sigma, USA) was intraperitoneally injected at a dose of 20 mg/kg body weight 1 h prior to LPS injection. The dosage of Mito-TEMPO is comparable with previous studies [ 28 , 29 ]. Animals were euthanized 24 h after LPS administration, and whole blood and liver samples were harvested for analysis.…”
Section: Methodssupporting
confidence: 88%
“…A previous study demonstrated that mito-TEMPO (MT) can ameliorate renal fibrosis by reducing oxidative stress, mitochondrial dysfunction, and inflammation (Liu et al, 2018 ). In addition, recent studies have shown that MT has a protective effect against acetaminophen-induced hepatotoxicity with a wider therapeutic time window than N-acetyl-L-cysteine (NAC; Du et al, 2017 ; Abdullah-Al-Shoeb et al, 2020 ). Systemic administration of MT was able to alleviate ischemic brain damage in rats (Li et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…All mice were sacrificed 24 h after APAP treatment, after which their blood and liver tissues were isolated for further analysis. The dosages of kahweol and APAP were determined based on previous studies [8,12]. All experimental protocols were approved by the Institutional Animal Care and Use Committee of the Daegu Catholic University Medical Center (approval number: DCIAFCR-200507-05-Y, approval date: 7 May 2020).…”
Section: Methodsmentioning
confidence: 99%